2019
DOI: 10.18203/2349-3291.ijcp20190037
|View full text |Cite
|
Sign up to set email alerts
|

Study of serum levels of CRP and procalcitonin as early marker of sepsis in children with sepsis above neonatal age group

Abstract: Background: Sepsis caused by infection remains a major cause of mortality and morbidity among children.  Blood culture though gold standard requires lot of time for diagnosis, hence it’s necessary to rely on early diagnostic markers such as blood counts, micro-ESR, CRP, Procalcitonin. The objective of this study is to evaluate the serum levels of CRP, Procalcitonin as reliable and as early marker of sepsis in pediatric patients above neonatal age group.Methods: Children aged above neonatal age group with clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Early identification of sepsis and prompt initiation of its therapy is the most important measure in reducing mortality from sepsis. Early identification of sepsis is difficult in children for many reasons, the clinical signs in children are very variable at the start of the infection; microbiological culture results are expected only after 48-72 hours; and false negative results are common [6]. In the current study, we found that concentrations were higher in septic patients than controls.…”
Section: Discussionmentioning
confidence: 44%
“…Early identification of sepsis and prompt initiation of its therapy is the most important measure in reducing mortality from sepsis. Early identification of sepsis is difficult in children for many reasons, the clinical signs in children are very variable at the start of the infection; microbiological culture results are expected only after 48-72 hours; and false negative results are common [6]. In the current study, we found that concentrations were higher in septic patients than controls.…”
Section: Discussionmentioning
confidence: 44%
“…The predictors of mortality included positive blood cultures, multiorgan dysfunction, late hospital admissions, severe acute malnutrition, and the requirement of supportive care [9,13,19]. The predictors of progression to septic shock were abnormal leukocyte count, neutrophil, temperature, culture positivity, severe acute malnutrition, CRP, and PCT [5,6,19,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis caused by infection remains a major cause of mortality and morbidity among children. Blood culture though the gold standard requires a lot of time for diagnosis; hence, it is necessary to rely on early diagnostic markers such as blood counts, CRP, and PCT [26]. CRP and PCT were the inflammatory markers for patients with clinically suspected sepsis.…”
Section: Discussionmentioning
confidence: 99%